Bamboo Dancing Method in Speaking Class for Eleventh Graders - Mujadid, Alief Jauhar; Ningrum, Ary Setya Budhi (English Education:Journal of English Teaching and Research, 2022)
The goal of this study is to see how effective the Bamboo Dancing Method is for teaching speaking skills. This study is quasi-experimental in which students in class XI SMAN 2 Pare were the focuses of this investigation. Class XI MIA 1 was the experimental group, and class XI MIA 7 was the control group. Pre-test and post-test in the form of speaking tests are employed for collecting data. In analyzing the data, ANCOVA was used to calculate the results. In the pre-test findings, the average value of the experiment was 53.00, while the control group mean was 54.00. The average value for the experiment on the post-test was 77.00, while the mean score for the control group was 73.83. According to the statistical calculation findings of ANCOVA, the results were significantly high, .000 < .05. Since the significance value is less than 0.05, it suggests that there is sufficient evidence to reject the null hypothesis; hence the alternative hypothesis is accepted. This indicates that employing the Bamboo Dancing Method to develop speaking skills is efficient.